THE EASTERLIN PARADOX IN ASEAN: WELFARE AND ECONOMIC GROWTH - Anggita Sari, Nastiti; Dolfriandra Huruta, Andrian; Robiyanto, Robiyanto (The European Journal of Applied Economics, 2025)
Achieving a prosperous condition is a final goal that the state wants to achieve. Welfare is a benchmark in assessing the progress of a country. Therefore, the objective of the article is to analyze the Economic Welfare in ASEAN countries. Gross Domestic Product (GDP) is currently used to quantify welfare objectively. However, happiness as subjective measure of well-being is used in this research. The System Generalized Method of Moments (SYS-GMM) is used to determine the elements that influence welfare in ASEAN. The data included the human development index, GDP per capita, unemployment rate, happiness index, and dependency ratio for the nine ASEAN countries between 2006 and 2023. Both the dependency ratio and GDP per capita significantly and favorably impact the happiness index. Given that GDP per capita has a positive impact on happiness, the Easterlin Paradox theory of happiness is applicable in ASEAN. Nevertheless, the happiness index is unaffected by the Human Development Index and unemployment. In order to achieve inclusive prosperity, ASEAN governments must, among other things, strengthen and expand regional collaboration in ASEAN’s major industries and in the areas of technology, health, and education.